Variazione del flusso diffusivo e migratorio di orso bruno (Ursus arctos Linneo 1758) dal Friuli Venezia Giulia verso il Veneto e ruolo ecologico delle aree transregionali. - FILACORDA, Stefano; FABRO, Carla (2005)
The Friuli Venezia Giulia region represents an important areas for the dispersion and recolonisation of the Brown Bear (Ursus arctos) from the Dinaric forests to the Italian Central Alps, where a small isolated population has survived and recently has been restocked. The signs of presence, cropped from 1970 to 2003 (n=374) by forestry corps and technicians, have been studied to describe the apparent tend and the numbers and size (convex polygon method, CPM, in ha) of hot spots, areas with a apparent high presence of Brown Bear from 19909 to 2001 (n= 260). The cluster analysis has identified 12 Hot spots (pseudo t2=30,0 R2 = 0,97, mean CPM = 12.908 ha), three of them area localised along the border between the Veneto and Friuli Venezia Giulia: Cansiglio (CPM = 692 ha), Barcis-Piancavallo (16.800 ha), Sauris-West carnian Alps area (17.860 ha), the last one represents an important post-denning area. From the time series analysis, the period with higher number of signs of presence, along the border Veneto-Friuli, has been from 1996 to 2000, respect the apparent increment of signs on Italian-Slovenia border observed in 1993 and in 1996-97. The process of recolonisation-diffusion, 60 km in 6 years, now seems to stop only 1 or 2 individuals, with a large home range, are established, in the transregional areas, between Friuli and Veneto. These areas need a special transregional conservation program, coupled to the transregional program with Slovenia for enhancing the creation or Brown Bear metapopulations.